Ignition probability and fuel consumption of boreal ground vegetation fuels : an experimental study in Finland - Lindberg, Henrik; Aakala, Tuomas; Vanha-Majamaa, Ilkka (Suomen metsätieteellinen seura, 2024)
In boreal forests fires often ignite and spread within the dominant moss and lichen cover of the ground layer vegetation, which thus greatly influences fire hazard. We used an experimental set-up in greenhouse conditions to study the differences in how (1) fuel moisture and (2) wind velocity influence the ignition probability and fuel consumption among four common circumboreal ground vegetation fuels, Pleurozium schreberi (Willd. ex Brid.) Mitt., Hylocomium splendens Schimp., Dicranum spp. and Cladonia rangiferina (L.) F. H. Wigg. Our results show that the reindeer lichen C. rangiferina was clearly the most flammable species, with high ignition probability even at high moisture contents and low wind velocities. Of the mosses, Dicranum was the least flammable, with low ignition probability and mass loss at low wind velocities regardless of moisture content. P. schreberi and H. splendens behaved somewhat similarly with wind velocities quickly increasing the initially low ignition probability and mass loss observed in the absence of wind. However, especially for mass loss, among-species differences tended to disappear with stronger winds. The observed differences can be explained by the different structures and growth forms of the studied species and open a potential avenue for improving forest fire risk predictions.
Keywords: forest fires; ground vegetation; prescribed burning; flammability; fuel moisture content; mass loss rate